2013
DOI: 10.1002/wmh3.75
|View full text |Cite
|
Sign up to set email alerts
|

Health Services Use Among Veterans Using U.S. Department of Veterans Affairs and Mainstream Homeless Services

Abstract: We examined the use of health and behavioral health services for two groups of homeless veterans (N ¼ 1,302) in the New York City area who were enrolled in the U.S. Department of Veterans Affairs (VA) healthcare system-veterans who use VA homeless programs, and veterans who use mainstream homeless programs only. Using administrative records from the VA and the New York City Department of Homeless Services, we compared the characteristics of users of VA and mainstream homeless programs and examined between-grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…However, despite their access to specialty care, homeless veterans were more likely to report emergency department visits in the past year. These findings are consistent with previous research reporting that 41% of their sample only used “mainstream” homelessness services and speak to a potential gap in the continuum of care for veterans. Specifically, homeless veterans appear to underutilize available outpatient and remote clinics that could reduce emergency department visits.…”
Section: Discussionsupporting
confidence: 91%
“…However, despite their access to specialty care, homeless veterans were more likely to report emergency department visits in the past year. These findings are consistent with previous research reporting that 41% of their sample only used “mainstream” homelessness services and speak to a potential gap in the continuum of care for veterans. Specifically, homeless veterans appear to underutilize available outpatient and remote clinics that could reduce emergency department visits.…”
Section: Discussionsupporting
confidence: 91%
“…A recent study found that more than one-third of a cohort of newly homeless veterans used mainstream homeless assistance services but did not access VHA homeless programs, suggesting that a sizable number of veterans experiencing homelessness or risk of homelessness (hereinafter referred to as "risk") may not be linked with VA resources that may improve their housing stability. 4 To improve the VA's ability to identify these veterans and refer them appropriately, VHA implemented a universal, two-question screener for current homelessness and imminent risk-the Homelessness Screening Clinical Reminder (HSCR)-that is administered at all VHA health-care facilities. During the first three months of its implementation (October 1, 2012, to January 10, 2013), 0.9% of respondents reported current homelessness, 1.2% reported imminent risk, and 97.9% screened negative for both.…”
mentioning
confidence: 99%
“…Our related publications preceding this issue addressed “Health Services Use Among Veterans Using U.S. Department of Veterans Affairs and Mainstream Homeless Services” (Byrne, Montgomery, Treglia, Roberts, & Culhane, ) and a practitioner report on “Ensuring Appropriate Discharge Practices for Hospitalized Homeless Patients” (Hochron & Brown, ). The 2014 Forum on Health, Homelessness and Poverty, and a planned event focusing on Global Food Security, will further these efforts to improve health by addressing its determinants in critical areas and informing policy and practice.…”
mentioning
confidence: 99%